Driven to lead good, bad, and misguided leadership - Lawrence, Paul R. (San Francisco Jossey-Bass, 2010)
The author applies the four drive theory of human behavior (to acquire, to defend, to comprehend, to bond) to the leadership realm, and explains the history of leadership in political, economic, and symbolic institutions as a result of one of three types of leadership: good leadership, misguided leadership; and evil leadership. This innovative book outlines a framework of human behavior that can be used to cultivate stellar leadership/leaders which balances the four drives while avoiding negative leadership and leaders who are missing the drive to bond"
Includes bibliographical references and index.
Keywords: Leadership